Innovation of VARK Modality-Based Differentiated Learning: Development of Social Studies Instructional Toolkit for Junior High School - Ismi Octaviani; Etin Solihatin; Uwes Anis Chaeruman (Integrated Science Education Journal, 2026)
Purpose of the study: The present study aimed to develop a differentiated instructional toolkit grounded in Neil Fleming's VARK (Visual, Aural, Read/Write, Kinesthetic) modalities for grade VII social studies, specifically on economic activity materials. Methodology: The study employed a Research and Development design following the ASSURE model (Analyze Learners, State Objectives, Select Methods, Media, and Materials, Utilize Media and Materials, Require Learner Participation, Evaluate and Revise). The research took place at SMP Nusantara 1 Tangerang and involved 79 grade VII students during the even semester of the 2025/2026 academic year. Data collection instruments included expert validation questionnaires, student response questionnaires, and pre-test/post-test assessments.Main Findings: The findings indicated that the developed instructional toolkit, which consisted of a teaching module, learning materials, student activity worksheets, interactive media, and assessment instruments, received a "highly feasible" rating from instructional design, content, and media experts. Student responses confirmed the practicality of the toolkit, as learners reported enhanced engagement when materials matched their preferred modalities. The effectiveness analysis demonstrated a significant improvement in learning outcomes, with the N-Gain score reaching the medium category (0.61). Novelty/Originality of this study: This study concludes that a VARK-based differentiated instructional toolkit serves as a valid, practical, and effective solution for improving social studies learning quality in junior high school settings.